(untitled) (Jurnal EurekaMatika, 2020)
The method used for production planning and inventory control in this research is a combination of Material Requirement Planning (MRP) and Mixed Integer Linear Programming (MILP) for produced materials. Meanwhile, for raw materials, the MRP method is used with the Wagner-Whitin Algorithm lot-sizing technique. Additionally, this study performs demand data forecasting using the exponential smoothing method. The objective of this research is to achieve a production and inventory system and schedule that are precise in terms of timing, quantity, and cost. To optimize time efficiency, a forecasting, production planning, and inventory control application program was constructed using the R programming language. The final result of this application construction is a web-based platform. Keywords: Combination of MRP and MILP methods, Inventory control, Production planning. ABSTRAK Metode yang digunakan untuk perencanaan produksi dan pengendalian persediaan pada penelitian ini adalah menggunakan kombinasi metode Material Requirement Planning dan Mixed Integer Linear Programing untuk bahan yang diproduksi. Sedangkan, untuk bahan baku menggunakan metode MRP dengan lotsizing Algoritma Wagner Within. Selain itu pada penelitian ini dilakukan juga proses peramalan data permintaan dengan metode exponential smoothing. Tujuan dari penelitian ini adalah supaya dicapai sistem serta jadwal produksi dan persediaan tepat waktu, jumlah, dan harga. Untuk mengefektifkan waktu, dilakukan konstruksi program aplikasi peramalan serta perencanan produksi dan pengendalian persediaan dengan menggunakan bahasa pemrograman R. Hasil konstruksi program aplikasi peramalan serta perencanaan produksi dan pengendalian persediaan berupa web.